2017
DOI: 10.18203/2349-3933.ijam20173253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients undergoing coronary angiography with special reference to complications of coronary angiography

Abstract: Background: Cardiovascular Diseases (CVD’s) remain the biggest cause of death worldwide. Recent trends suggest that disease incidence has escalated and has started affecting younger age group also. Incidence of CVD’s has been on increasing trend not only in urban areas but in rural areas also. Aim of this research is to study clinical profile and complications in patients undergoing coronary angiography.Methods: 100 patients admitted in hospital who were planned for coronary angiography were selected. All rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…3 Despite the efforts of medical research and governments in reducing this health burden, recent trends have shown that the disease incidence has escalated and has started affecting a younger age group. 4 A variety of tests can assist in the diagnosis of CAD electrocardiography, stress testing, echocardiography, chest X-rays, and laboratory blood tests. Coronary angiography is considered to be the "gold standard" for the diagnosis of CAD as it is used to identify the precise location and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite the efforts of medical research and governments in reducing this health burden, recent trends have shown that the disease incidence has escalated and has started affecting a younger age group. 4 A variety of tests can assist in the diagnosis of CAD electrocardiography, stress testing, echocardiography, chest X-rays, and laboratory blood tests. Coronary angiography is considered to be the "gold standard" for the diagnosis of CAD as it is used to identify the precise location and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%